2013
DOI: 10.1016/j.jtcvs.2012.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Hemi–aortic arch debranching for hybrid aortic arch repair by sequential transposition of the left common carotid and subclavian arteries

Abstract: Hybrid aortic arch repair by sequential transposition of the left common carotid artery and of the left subclavian artery for zone 1 lesions provides an attractive alternative for treating hemi-aortic arch lesions in high-risk patients with minimal atherosclerotic disease in the aorta and great vessels with acceptable primary results and encouraging midterm efficacy to prevent rupture. This hybrid strategy avoiding prosthetic bypass offers several advantages over conventional repair, including the potential to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…This finding confuses the comparison of operative mortality between reports and suggests studies which only report in-hospital mortality may significantly underestimate 30-day/in-hospital mortality. Nonetheless, the procedure-specific 30-day/in-hospital mortality rates in this study are comparable to prior reports of zone 1 hybrid arch repair (0%-15.6%), 11, 12, 17, 18 zone 0 hybrid arch repair (8.5%-29.6%), 9-12, 14, 17, 20 stented elephant trunk completion (4.5%-11%), 1, 2, 6, 7, 13 and total arch replacement with stented elephant trunk completion (17%). 7 …”
Section: Discussionsupporting
confidence: 87%
“…This finding confuses the comparison of operative mortality between reports and suggests studies which only report in-hospital mortality may significantly underestimate 30-day/in-hospital mortality. Nonetheless, the procedure-specific 30-day/in-hospital mortality rates in this study are comparable to prior reports of zone 1 hybrid arch repair (0%-15.6%), 11, 12, 17, 18 zone 0 hybrid arch repair (8.5%-29.6%), 9-12, 14, 17, 20 stented elephant trunk completion (4.5%-11%), 1, 2, 6, 7, 13 and total arch replacement with stented elephant trunk completion (17%). 7 …”
Section: Discussionsupporting
confidence: 87%
“…Debranching and revascularization in zone 1 were mainly performed through cervico-manubriotomy with sequential transposition of the LCCA and the LSA as we previously described. 8 For patients deemed unsuitable for sequential transposition because of proximal atherosclerotic lesions of the supra-aortic trunks, extra-anatomic revascularization of LCCA and LSA was performed with a carotid-carotid bypass, followed by a left carotid-subclavian transposition. Debranching and revascularization in zone 2: Revascularization of the LSA was performed each time it was possible without regard to vertebral circulation.…”
Section: Debranching Proceduresmentioning
confidence: 99%
“…Canaud et al, from France, reported 11 cases treated with sequential transposition of left carotid and subclavian arteries via partial upper sternotomy and left cervical extension. 21 They had 90.9% technical success and no perioperative mortality. One patient had retrograde type A dissection requiring immediate surgical aortic root replacement with circulatory arrest.…”
Section: Arch Debranchingmentioning
confidence: 95%